Efikasi Herbisida Isopropil Amina Glifosat 480 g/l Terhadap Gulma Pada Persiapan Lahan Sawah Dengan Sistem Tanpa Olah Tanah Dan Pengaruhnya Terhadap Tanaman Padi - Rifa'i, Thaher; Susanto, Herry; Nurmauli, Niar; Pujisiswanto, Hidayat (Universitas Lampung, 2023)
One of the efforts to control weeds in preparing land for lowland rice cultivation with the No-Tillage system one of which uses isopropylamineglyphosate herbicide. The purpose of this study was to determine the dose of glyphosate herbicide that effectively controls weeds for preparation of lowland rice planting with the no tillage system, to determine changes in weed composition in lowland rice after the application of glyphosate herbicide, and to determine the effect of the no tillage system after the application of glyphosate herbicide on growth and paddy yields. Data collection was carried out from June to September 2022 in the rice fields of Trimurjo District, Central Lampung Regency and the Weed Science Laboratory, Faculty of Agriculture, University of Lampung. The treatment was arranged using a randomized block design with 4 replications and 6 treatments consisting of the glyphosate herbicide doses (1,080; 1,440; 1,800; 2,160 g/ha) + no tillage, manual weeding, and intensive tillage system. Homogeneity of variance was tested by Barlett's test and then analyzed for variance. Separation of the mean was carried out using the least significant difference test (LSD) at the 5% level. The results showed that the herbicide isopropylamine glyphosate doses of 1,800 and 2,160 g/ha of the no tillage system could be used to replace the intensive tillage system because it was effective in controlling total weeds, sedges, grasses, and broad leaf groups, dominant weed Fimbristylis miliacea, Echinochloa colonum, Ludwigia octovalvis and Monochoria vaginalis up to 6 WAP, causing a change in the composition of weed species from Echinochloa colonum become monochoria vaginalis at 3 WAP, and from Echinochloa colonum become Ludwigia octovalvis at 6 WAP. The growth is not stunted and yield of lowland rice plants is equivalent to the intensive tillage system with grain yields per hectare of 5.14 - 5.49 t/ha. Key words : weeds, isopropylamine glyphosate, paddy field, no tillage